TNF and TNF Receptor Superfamily Members in HIV infection: New Cellular Targets for Therapy?. (19th December 2013) - Kumar, Amit; Abbas, Wasim; Herbein, Georges
Abstract : Tumor necrosis factor (TNF) and TNF receptors (TNFR) superfamily members are engaged in diverse cellular phenomena such as cellular proliferation, morphogenesis, apoptosis, inflammation, and immune regulation. Their role in regulating viral infections has been well documented. Viruses have evolved with numerous strategies to interfere with TNF-mediated signaling indicating the importance of TNF and TNFR superfamily in viral pathogenesis. Recent research reports suggest that TNF and TNFRs play an important role in the pathogenesis of HIV. TNFR signaling modulates HIV replication and HIV proteins interfere with TNF/TNFR pathways. Since immune activation and inflammation are the hallmark of HIV infection, the use of TNF inhibitors can have significant impact on HIV disease progression. In this review, we will describe how HIV infection is modulated by signaling mediated through members of TNF and TNFR superfamily and in turn how these latter could be targeted by HIV proteins. Finally, we will discuss the emerging therapeutics options based on modulation of TNF activity that could ultimately lead to the cure of HIV-infected patients.